Restorative Justice Based On An Islamic Legal Perspective In Cases Of Children As Criminal Offenders - Anwar Mayer Siregar (Warmadewa Press, 2025)
Most criminal cases in Indonesia adhered to the revenge theory, this has an impact on overloaded prisons and detention centers. Islamic law, one of Indonesia's oldest laws after law customs, apparently has also regulated restorative justice. Principle restorative justice in law Islam uses draft qisas and diyat payment. This study examines the regulation and implementation of restorative justice in Islamic law, with a focus on protecting the rights of child offenders. This research uses a normative research method using a conceptual approach, namely an approach that analyzes the resolution of a problem. The results obtained from this research conclude that there is also a concept of restorative justice in Islamic law, which differentiates between the two only in terms. In Islamic law, restorative justice is often called forgiveness and diyat. Both are dispute resolution methods through non-litigation and require a third party as a mediator. Resolving children's problems using the concept of restorative justice is very appropriate if implemented in cases of children who commit criminal acts.